Hot spots for GPCR signaling: lessons from single-molecule microscopy. (April 2019) - Calebiro, Davide; Jobin, Marie-Lise
Highlights: Single-molecule microscopy provides unique opportunities to study GPCR signaling. New single-molecule data show that receptor–G protein interactions last 1–2 s. Agonists increase the association rate between receptors and G proteins. The receptor–G protein association rate correlates with agonist efficacy. Receptors interact with G proteins at hot spots on the plasma membrane. Abstract : G protein-coupled receptors (GPCRs) are among the best-studied membrane receptors, mainly due to their central role in human physiology, involvement in disease and relevance as drug targets. Although biochemical and pharmacological studies have characterized the main steps in GPCR signaling, how GPCRs produce highly specific responses in our cells remains insufficiently understood. New developments in single-molecule microscopy have made it possible to study the protein–protein interactions at the basis of GPCR signaling in previously inconceivable detail. Using this approach, it was recently possible to follow individual receptors and G proteins as they diffuse, interact and signal on the surface of living cells. This has revealed hot spots on the plasma membrane, where receptors and G proteins undergo transient interactions to produce rapid and local signals. Overall, these recent findings reveal a high degree of dynamicity and complexity in signaling by GPCRs, which provides a new basis to understand how these important receptors produce specific effects and might pave the way to innovative pharmacological approaches.